Improving the Yield and Quality of Daptomycin in Streptomyces roseosporus by Multilevel Metabolic Engineering - Lyu, Zhong-Yuan; Bu, Qing-Ting; Fang, Jiao-Le; Zhu, Chen-Yang; Xu, Wei-Feng; Ma, Lie; Gao, Wen-Li; Chen, Xin-Ai; Li, Yong-Quan (Frontiers in Microbiology, 2022)
Daptomycin is a cyclic lipopeptide antibiotic with a significant antibacterial action against antibiotic-resistant Gram-positive bacteria. Despite numerous attempts to enhance daptomycin yield throughout the years, the production remains unsatisfactory. This study reports the application of multilevel metabolic engineering strategies in Streptomyces roseosporus to reconstruct high-quality daptomycin overproducing strain L2797-VHb, including precursor engineering (i.e., refactoring kynurenine pathway), regulatory pathway reconstruction (i.e., knocking out negative regulatory genes arpA and phaR), byproduct engineering (i.e., removing pigment), multicopy biosynthetic gene cluster (BGC), and fermentation process engineering (i.e., enhancing O2 supply). The daptomycin titer of L2797-VHb arrived at 113 mg/l with 565% higher comparing the starting strain L2790 (17 mg/l) in shake flasks and was further increased to 786 mg/l in 15 L fermenter. This multilevel metabolic engineering method not only effectively increases daptomycin production, but can also be applied to enhance antibiotic production in other industrial strains.